Peran Literasi Fintech Syariah Terhadap Kasus Pinjaman Online Legal Maupun Ilegal - Nike Nur'aini; Selasi, Dini; Pratama, Gama; Ridwan, Mohammad (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The development of fintech, on the one hand, has facilitated transaction activities, but on the other, it also raises many problems that arise in Indonesian society. This is especially the case in peer-to-peer lending (P2PL). Based on the phenomenon that people who use pinjol have problems like being arrested, paying off their debts with hole-covering holes, and some committing suicide. This research aims to make the public aware of the importance of Shariah fintech literacy so that it is not easily affected by online loan offers, both legal and illegal. This method uses qualitative methods because the process is carried out by analyzing and studying the theory of the role of fintech literacy and phenomena related to online loan cases that occur in Indonesian society indirectly from secondary data. The results of this study show that the more a person understands the fintech literacy of Shariah, the more they will be protected from the negative impact of online loans, both legal and illegal.